2021
DOI: 10.48550/arxiv.2108.09844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brown measure of the sum of an elliptic operator and a free random variable in a finite von Neumann algebra

Abstract: We obtain, under mild assumptions, a formula for the Brown measure of the sum of a twisted elliptic operator g t,γ with an arbitrary random variable x 0 , freely independent from g t,γ . The twisted elliptic operators include Voiculescu's circular operator and elliptic operators. We show that the Brown measure of the sum of a twisted elliptic operator with a free random variable is the push-forward measure of the Brown measures of the sum of a free circular operator with the same free random variable under a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…They also show that all the Brown measures obtained by varying τ with s and u fixed are related. (4) The paper [27] of Zhong considers the additive counterpart z s,τ of b s,τ and uses free probability to compute the Brown measure of x 0 + z s,τ , where x 0 is freely independent of z s,τ . In the case that x 0 is Hermitian, Zhong relates all the Brown measures obtained by varying τ with s and x 0 fixed.…”
Section: The Model Deformation Phenomenon In Random Matrix Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…They also show that all the Brown measures obtained by varying τ with s and u fixed are related. (4) The paper [27] of Zhong considers the additive counterpart z s,τ of b s,τ and uses free probability to compute the Brown measure of x 0 + z s,τ , where x 0 is freely independent of z s,τ . In the case that x 0 is Hermitian, Zhong relates all the Brown measures obtained by varying τ with s and x 0 fixed.…”
Section: The Model Deformation Phenomenon In Random Matrix Theorymentioning
confidence: 99%
“…The circular-to-semicircular conjecture is the case X N 0 = 0, τ 0 = 1, and τ = 0, while the semicircular-to-circular conjecture is the case X N 0 = 0, τ 0 = 0, and τ = 1. The limiting eigenvalue distribution of X N 0 + Z N s,τ , meanwhile, has been computed by Zhong [27] using methods of free probability. See also similar results in [15] obtained by the PDE method.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…In [24], the author calculated the Brown measure density of g t + u. It is showed that the Brown measure of g t + u is the pushforward measure of c t + u under some natural pushforward map.…”
Section: Some Miscellaneous Applicationsmentioning
confidence: 99%